Kajian Ikonografi Masjid Al Ahdhar Bekasi - Qonita, Sania; Alimin, Nurhayatu Nufut (Institut Teknologi Nasional, Bandung, 2023)
Al Ahdhar Mosque is a modern mosque that has a different shape than other mosques. This results in various public perceptions of the shape of the mosque, both positive and negative. To find out the meaning behind these forms, a study was conducted to determine the factual meaning of the visible icons in the architecture and interior of the Al Ahdhar Mosque. This research uses a descriptive qualitative method with Erwin Panofsky's iconographic approach. Data collection techniques were carried out through interviews, observations, and literature studies. Based on the research that has been done, the results showed that there is a meaning behind the icons in the architecture and interior of the mosque related to the green concept and Islamic teachings.Â In mosque architecture, the asymmetrical shape is an analogy of prostration in prayer, while the large opening in the interior is a manifestation of the implementation of an open concept.Â Based on the presentation of the mosque's visuals and the meaning behind it, the Al Ahdhar Mosque uses a contemporary modern style.